KRITIK ISLAM TERHADAP MATERIALISME - Harsa Tri mona; Moch Iqbal (DIALEKTIKA, 2022)
Materialism is a flow of philosophy that considers the material needs on the ideology of ideology, spiritual, social, and cultural religion. Materialism that is an ideology is quite growing rapidly especially in the West. Materialism is basically not a new stream, or the result of modern times, but the confidence of this flow, has existed since the ancient Greek philosophical age. Some of the materialists of Western materials consider the development of the flow along with the progress of science. As the material growth is very related to the development of science. The background of development of the materialism in the West is different from the development of materialism in the Islamic world both history and the context of the ordination doctrine. Among these factors are the first, the weakness of the doctrines of church and the arrogance and the violence he does. Second, the weakness of the Western ideas. This paper is a literature study by lacking data from sources relevant to discussion. After the study must be obtained by the result that the archogetry of the materialists does not match the teachings of Islam